A Comparative Study of the Land Administration and the Document Authentication Agencies on the Influence of Reform Management on Organizational Culture Change - Gebretsadik, Simret (African Journal of Leadership and Development, 2020)
For the past two decades, Ethiopia was engaged in changing her public service sector culture from bureaucratic to market type. The reform program was introduced in to all Ethiopian public service organizations simultaneously and using the same change tools. However, except in few organizations, the reform did not result in organizational culture change. DARA is one of the few organizations known for their reform success and LDMB is one of the many organizations identified with unfruitful reform efforts. The objective of this study was to investigate influence of reform management on organizational culture change in the cases of DARA and LDMB. The research methodology of the study was based on a pragmatic worldview followed by convergent parallel mixed methods approach. Quantitative data were collected from 130 leaders and 435 employees of DARA and LDMB. Besides,qualitative data were gathered via interviews and document review. Data analysis was done using PLS-SEM, Mann-Whitney U test, Binomial logistic regression, percentages and narration. Findings revealed that, eventhough Kotters’ change management model has mishandled organizational culture, its strict application has resulted in culture change at DARA. Factors that have contributed to DARA’s reformare success are availability of resources, leadership’s competence in change management, existence of feltneed for change and prevalence of leadership autonomy. Therefore, the study concluded that the way reform is managed in a certain organization determines the level of organizational culture change to be obtained in the same. To that end, Kotter’s change management model needs to be modified so that it could enable organizations manage organizational culture change effectively.